Breg Cells in Celiac Disease Isolated or Associated to Hashimoto's Thyroiditis. (8th October 2018) - Santaguida, Maria Giulia; Gatto, Ilenia; Mangino, Giorgio; Virili, Camilla; Stramazzo, Ilaria; Fallahi, Poupak; Antonelli, Alessandro; Gargiulo, Patrizia; Romeo, Giovanna; Centanni, Marco
Abstract : Hashimoto's thyroiditis (HT) may occur associated with celiac disease (CD). Regulatory B cells (Breg) subsets have been shown to play a significant role in autoimmune processes. Therefore, we have characterized their distribution in the peripheral blood obtained from 10 patients with isolated HT, 10 patients with HT + CD, 9 patients with isolated CD, and 9 healthy donors (HD). Th17 cells were significantly increased in patients with HT and in patients bearing both HT and CD, while patients with isolated CD exhibited a lower percentage of Th17, as compared with healthy donors. CD24 hi CD38 hi Breg cells were significantly higher in patients with HT + CD and in patients with isolated CD as compared to both HD patients and patients with isolated HT (p = 0.0010 ). On the contrary, Breg memory phenotypes (CD24 hi CD38 − and CD24 hi CD27 + ) significantly decreased in patients with HT + CD as compared with the isolated disorders. Following CpG oligodeoxynucleotide stimulation, IL-10 + CD24 hi CD38 hi Breg cells were similar in all groups of patients, despite these cells would have been higher in CD patients. In conclusion, celiac disease, isolated and even more when associated with HT, determines a peculiar behavior of Breg cells which are increased in number but possibly functionally defective. Furthermore, the association CD + HT was characterized by a reduction of Breg memory subsets as compared with the isolated disorders. The behavior of Th17 subset in patients with celiac disease associated with HT might have been sensitive to the effect of long-lasting GFD, and it is essentially determined by the presence of thyroid autoimmunity.